Association of Nonribosomal Nucleolar Proteins in Ribonucleoprotein Complexes during Interphase and Mitosis - Piñol-Roma, Serafín (The American Society for Cell Biology, 1999)
rRNA precursors are bound throughout their length by specific proteins, as the pre-rRNAs emerge from the transcription machinery. The association of pre-rRNA with proteins as ribonucleoprotein (RNP) complexes persists during maturation of 18S, 5.8S, and 28S rRNA, and through assembly of ribosomal subunits in the nucleolus. Preribosomal RNP complexes contain, in addition to ribosomal proteins, an unknown number of nonribosomal nucleolar proteins, as well as small nucleolar RNA-ribonucleoproteins (sno-RNPs). This report describes the use of a specific, rapid, and mild immunopurification approach to isolate and analyze human RNP complexes that contain nonribosomal nucleolar proteins, as well as ribosomal proteins and rRNA. Complexes immunopurified with antibodies to nucleolin—a major nucleolar RNA-binding protein—contain several distinct specific polypeptides that include, in addition to nucleolin, the previously identified nucleolar proteins B23 and fibrillarin, proteins with electrophoretic mobilities characteristic of ribosomal proteins including ribosomal protein S6, and a number of additional unidentified proteins. The physical association of these proteins with one another is mediated largely by RNA, in that the complexes dissociate upon digestion with RNase. Complexes isolated from M-phase cells are similar in protein composition to those isolated from interphase cell nuclear extracts. Therefore, the predominant proteins that associate with nucleolin in interphase remain in RNP complexes during mitosis, despite the cessation of rRNA synthesis and processing in M-phase. In addition, precursor rRNA, as well as processed 18S and 28S rRNA and candidate rRNA processing intermediates, is found associated with the immunopurified complexes. The characteristics of the rRNP complexes described here, therefore, indicate that they represent bona fide precursors of mature cytoplasmic ribosomal subunits.